Cultural Transformation through Digitalization: A Bibliometric Approach in Responding to Changes in Social Values, Norms, and Cultural Practices in Society - Loso Judijanto; Mei Rani Amalia; Arief Fahmi Lubis; Weda Febriyanto (West Science Social and Humanities Studies, 2024)
This study employs VOSviewer to conduct a bibliometric analysis and visualize the intricate research landscape surrounding the themes of digitalization, cultural transformation, organizational practices, and the impact of global crises like the COVID-19 pandemic. Through a series of network density maps, the research identifies key thematic concentrations and academic collaborations over recent years. It reveals how digitalization intersects with various societal dimensions, influencing education, cultural heritage, sustainability, and business practices. The analysis emphasizes the role of digital technologies in facilitating significant social and organizational changes, advocating for policies that enhance digital literacy and inclusivity. Additionally, the examination of authorship networks sheds light on influential scholars and collaborative dynamics, providing insights that can guide future research directions. The study underscores the necessity for adaptive business models that integrate sustainability and resilience, crucial for navigating contemporary and future challenges.